2001
DOI: 10.1046/j.1471-4159.2001.t01-1-00218.x
|View full text |Cite
|
Sign up to set email alerts
|

beta-Amyloid-induced neuronal apoptosis requires c-Jun N-terminal kinase activation

Abstract: beta-Amyloid (A beta) has been strongly implicated in the pathophysiology of Alzheimer's disease (AD), but the means by which the aggregated form of this molecule induces neuronal death have not been fully defined. Here, we examine the role of the c-Jun N-terminal kinases (JNKs) and of their substrate, c-Jun, in the death of cultured neuronal PC12 cells and sympathetic neurons evoked by exposure to aggregated A beta. The activities of JNK family members increased in neuronal PC12 cells within 2 h of A beta tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
171
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(180 citation statements)
references
References 47 publications
9
171
0
Order By: Relevance
“…In primary hippocampal neurons, the levels of active JNK and phosphorylated IRS1 (Ser616) and tau (Ser422) are significantly increased by exposure to Aβ oligomers (Shoji et al ., 2000). Conversely, JNK inhibition is capable of reducing Aβ toxicity and ameliorating the major pathological features of AD (Troy et al ., 2001; Zhou et al ., 2015). In the present study, we found that intranasal insulin was revealed to target JNK activation in APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…In primary hippocampal neurons, the levels of active JNK and phosphorylated IRS1 (Ser616) and tau (Ser422) are significantly increased by exposure to Aβ oligomers (Shoji et al ., 2000). Conversely, JNK inhibition is capable of reducing Aβ toxicity and ameliorating the major pathological features of AD (Troy et al ., 2001; Zhou et al ., 2015). In the present study, we found that intranasal insulin was revealed to target JNK activation in APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the lack of effect of the c-Jun antisense oligonucleotide on caspase-2 and -3 activations lies, in contrast, with the previously reported inhibition of these caspases upon treatment with CEP-1347, an inhibitor of the c-Jun N-terminal kinase (JNK). 19,58 It could thus be postulated that the effect of CEP-1347 on these two caspases reflected disruption of the JNK action on a target different from c-Jun, such as activating transcription factor 2 or Elk1. 59 It should also be noticed that, despite its lack of effect on the activation of caspase-2 and -3, the c-Jun antisense oligonucleotide afforded protection of cortical neurons against Ab-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Moreover, both c-Jun expression and activation were found to be increased following exposure of neurons to Ab, and recent data suggested a 12-Lipoxygenase and amyloid peptide toxicity A Lebeau et al critical role of this transcription factor in Ab-induced apoptosis. [17][18][19]43,44 We therefore investigated whether 12-LOX blockade could interfere with such an Ab-induced c-Jundependent apoptotic pathway in cortical cells.…”
Section: Blockade Of 12-lox Expression Disrupts a C-jun-dependent Ab-mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the apoptotic process does not occur in JNK-knockout mice [222] or mice expressing a mutant form of c-Jun lacking the JNK phosphorylation site [15]. In addition, the indirect inhibition of JNK by CEP-1347 protected neuronal PC12 cells and sympathetic neurons in vitro from death following trophic factor withdrawal, beta-amyloid exposure, UV-radiation and oxidative stress [126,205]. Furthermore, CEP-1347 protected nigral neurons in vivo against MPP + -induced neuronal death [173] implicating again the involvement of JNK in neurodegeneration.…”
Section: Map Kinase Signalingmentioning
confidence: 99%